Clinical, pathological, and genotypic analysis of infectious bronchitis virus in broiler chickens in the Abu Dhabi Emirate, United Arab Emirates - Ishag, Hassan Zackaria Ali; Terab, Abdelnasir Mohammed Adam; Osman, Ebrahim Mohamad Abdalsalam; El Tigani-Asil, El Tigani Ahmed; Albreiki, Mohammed Saleh; Bensalah, Oum Keltoum; Shah, Asma Abdi Mohamed; Khalafalla, Abdelmalik Ibrahim (Frontiers in Veterinary Science, 2025)
BackgroundInfectious Bronchitis (IB), caused by the infectious bronchitis virus (IBV), is a significant contagious respiratory disease in the poultry industry. The emergence of new variants represents a global challenge for the diagnosis and control of the disease. Despite vaccination efforts in poultry farms in the Abu Dhabi Emirate, United Arab Emirates (UAE), outbreaks continue to occur, raising concerns about the efficacy of vaccination protocols and the potential emergence of new viral strains. This study aims to provide information on clinical, pathological, and genotypes of IBV detected within the Abu Dhabi Emirate, during 2022–2023.MethodsEpidemiological data were collected from twelve suspected IB outbreaks across seven broiler farms located in the Abu Dhabi Emirate. The cases were investigated through clinical and pathological examinations and Forty-six samples, including lung, spleen, kidney tissues, and oro-cloacal swabs, were collected for further analysis. The virus was detected by RT-qPCR assay, genotyping was determined by phylogenetic analysis of the Spike (S)-1 gene, and differentiation between field and vaccine strains was determined by comparing their sequences.ResultsThe age of the affected flocks varies from 2 to 5 weeks. The highest morbidity, mortality and case fatality rates were 36, 33, and 95%, respectively. Necropsy examination revealed characteristic respiratory and renal pathological lesions. Phylogenetic analysis revealed a co-circulation of three lineages of IBV genotype GI-13 or 4/91 serotype (81.8%), GI-1 or Massachusetts serotype (9.1%) and GI-23 or Middle East serotype (9.1%). Approximately 90.9% of the strains classified within GI-1 and G1-13 lineages are 99 to 100% identical to 4/91 and Mass serotypes, respectively, and are considered as vaccine strains. Two strains (9.1%) classified within GI-23 lineage have a < 99% identity to the 4/91 and Mass serotypes vaccine strains and are considered as filed strains.ConclusionCo-circulation of three IBV lineages (GI-13, GI-1, and GI-23) in the Abu Dhabi broiler flocks showing IB symptoms were detected. This complex scenario of different IBV lineages circulation may account for the persistent outbreaks despite vaccination efforts. The results of the study are crucial for optimum IB vaccination and monitoring strategies or designing new vaccines based on local IBV field strains.